HUBUNGAN ANTARA PENGETAHUAN PERAWATAN LUKA PASCA BEDAH SECTIO CAESAREA (SC) DENGAN TINGKAT KEMANDIRIAN PASIEN DI RUANG INSTALASI RAWAT INAP KEBIDANAN DAN KANDUNGAN RUMAH SAKIT BHAYANGKARA MANADO - Rahim, Wahyuni Abd.; Rompas, Sefti; Kallo, Vandri D. (JURNAL KEPERAWATAN, 2019)
Abstract: Caesarean section is defined as the birth of the fetus through an incision in theabdominal wall and uterine wall. The knowledge mother after giving birth with sectioncaesarean regarding nursing determine the ability of the mother to take care of herselfindependently so that the mother is able to monitor change that occur in her after giving abirth. The purpose of this research was to determine the relationship between the knowledgeof wound care postoperative caesarean section with the level of ndependance of patients in theobstetric and gynecology inpatient installation room at Bhayangkara Hospital, Manado.Research design of this research uses a type of descriptive research with a cross sectionalapproach. The number of samples were 32 people with purposive sampling technique. Thedata was collected using questionnaire and the analysis of the data using Fishers Exactstatistical test. The results showed that the knowledge of wound care in postoperativecaesarean section mothers was good (81,2%), most of them had independent levels ofindependence (65,6%) and were less independent (34,4%) and where p = 0,011 < 0,05.Conclusion there is a significant relationship between knowledge of wound care postoperativesection caesarean with the level of independence of patients at the nursing room of theBhayangkara Hospital, Manado.Keywords: Wound Care, Caesarean Section, Level of IndependenceAbstrak: Sectio caesarea didefinisikan sebagai lahirnya janin melalui insisi didindingabdomen dan dinding uterus. Pengetahuan ibu setelah melahirkan dengan sectio caesareamengenai perawatan dapat menentukan kemampuan ibu dalam merawat diri secara mandirisehngga ibu mampu memantau perubahan yang terjadi pada dirinya setelah melahirkan.Tujuan penelitian ini bertujuan untuk mengetahui hubungan antara pengetahuan perawatanluka pasca bedah sectio caesarea dengan tingkat kemandirian pasien di ruang Instalasi RawatInap Kebidanan dan Kandungan RS Bhayangkara Manado. Desain Penelitian jenis penelitianini menggunakan jenis penelitian deskriptif dengan pendekatan cross sectional. Jumlah sampel32 orang dengan menggunakan teknik sampel purposive sampling. Alat pengumpulan datasberupa kuesioner. Analisa data menggunakan uji statistik Fishers Excat. Hasil Penelitiandidapatkan bahwa pengetahuan perawatan luka pada ibu pasca bedah sectio caesarea baik(81,2%), sebgaian besar memiliki tingkat kemandirian mandiri (65,6%) dan kurang mandiri(34,4%) dan dimana p = 0,011 < 0,05. Kesimpulan terdapat hubungan yang signifikan antarapengetahuan perawatan luka pasca bedah sectio caesarea dengan tingkat kemandirian pasiendi ruang instalasi rawat RS Bhayangkara Manado.Kata Kunci: Perawatan Luka, Sectio Caesarea, Tingkat Kemandirian